The Effect of Religiosity on Pro-environmental Behavior Based on the Theory of Planned Behavior: A Cross-Sectional Study Among Iranian Rural Female Facilitators - Karimi, Saeid; Liobikienė, Genovaitė; Alitavakoli, Fatemeh (Frontiers in Psychology, 2022)
Religiosity is one of the most prominent and extensive social factors influencing one’s behavior; however, there is a lack of research analyzing the religiosity impact on pro-environmental behavior, particularly for women in rural areas. To narrow the research gap, this study established a theoretical research model by incorporating religiosity into the Theory of Planned Behavior to explore factors affecting rural female facilitators’ pro-environmental behavior. The extended Theory of Planned Behavior model was consequently tested by empirical data collected from 110 rural female facilitators in Qom Province in the center of Iran. The results of structural equation modelling indicated that subjective norms and environmental attitude were positively and significantly related to pro-environmental intentions. In addition, pro-environmental intentions and perceived behavioral control were found to be significantly associated with pro-environmental behaviors. The results revealed that there was a direct and indirect relationship between religiosity and pro-environmental behaviors via perceived behavioral control. In addition, there was an indirect relationship between religiosity and pro-environmental intentions via subjective norms and environmental attitudes. Therefore, this study revealed that religiosity as social pressure plays an important role in determining pro-environmental intentions and behaviors among rural female facilitators in Iran. Thus, in order to promote pro-environmental behavior, the religiosity aspects should be considered and people should be stimulated to act in a more environmentally friendly mode via religious prism.